Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

f(x) = 4x^3 + 7x^2 – 2x – 1
g(x) = 4x – 2
Find (f -g)(x).


Sagot :

Space

Answer:

(f - g)(x) = 4x³ + 7x² - 6x + 1

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = 4x³ + 7x² - 2x - 1

g(x) = 4x - 2

(f - g)(x) is f(x) - g(x)

Step 2: Find (f - g)(x)

  1. Substitute:                              (f - g)(x) = 4x³ + 7x² - 2x - 1 - (4x - 2)
  2. Distributive -1:                         (f - g)(x) = 4x³ + 7x² - 2x - 1 - 4x + 2
  3. Combine like terms:              (f - g)(x) = 4x³ + 7x² - 6x + 1